Modified activated carbon as well as preparation method and application thereof

Through activation reaction, copper salt impregnation and microwave treatment of modified activated carbon, the problems of high load capacity and heavy metal ions residue in the metal loading method are solved, and a highly efficient adsorption performance and environmentally friendly modified activated carbon preparation are achieved.

CN119455898APending Publication Date: 2025-02-18CHINESE RES ACAD OF ENVIRONMENTAL SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411765494.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing metal-loaded modified activated carbon has the problems of high loading and the residual heavy metal ions after impregnation, which will cause secondary pollution to the environment.

Method used

By mixing activated carbon with acid for activation reaction, then impregnating in copper salt solution, and using microwave treatment to change the activated carbon pore structure to form copper oxides, and finally obtain modified activated carbon.

Benefits of technology

This method does not require high-temperature calcination treatment, short microwave treatment time, reduces energy consumption, avoids resource waste, and significantly improves the adsorption performance of activated carbon. There is no residual heavy metal ion in the treated water, avoiding secondary pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455898A_ABST
    Figure CN119455898A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of activated carbon, in particular to modified activated carbon as well as a preparation method and application thereof. The method comprises the following steps: mixing activated carbon with acid, and performing activation reaction to obtain pretreated activated carbon; dipping the pretreated activated carbon in a copper salt solution to obtain activated carbon loaded with copper ions; mixing the active carbon loaded with the copper ions with water, and performing microwave treatment to obtain the modified active carbon. According to the prepared modified activated carbon, the doping amount of copper metal is only about 0.7%, and the problem that residual heavy metal ions cause secondary pollution to the environment is solved while the excellent sulfadimidine removal capacity is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of activated carbon preparation, and in particular to modified activated carbon and a preparation method and application thereof. Background Art

[0002] Activated carbon (AC) can effectively remove odor, color, some inorganic compounds and most organic pollutants due to its large specific surface area and complex pore structure. However, its use in practical applications is limited due to its low adsorption efficiency and cost constraints. The metal loading method is a common activated carbon modification method. The metal loading method often uses impregnation, impregnation precipitation, impregnation calcination, melt-gel method and other methods to load specific metals and metal compounds on the surface and pore structure of activated carbon in the form of molecules to enhance its adsorption performance. However, the current metal loading method has the problem of high loading capacity, and the residual heavy metal ions after impregnation will cause secondary pollution to the environment. Summary of the invention

[0003] The purpose of the present invention is to provide a modified activated carbon and a preparation method and application thereof, so as to solve the problem that the current metal loading method has a high loading amount and the residual heavy metal ions after impregnation will cause secondary pollution to the environment.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing modified activated carbon, comprising the following steps:

[0006] 1) Mixing activated carbon with acid to perform activation reaction to obtain pretreated activated carbon;

[0007] 2) impregnating the pretreated activated carbon in a copper salt solution to obtain activated carbon loaded with copper ions;

[0008] 3) Mixing the copper ion-loaded activated carbon with water and subjecting it to microwave treatment to obtain modified activated carbon.

[0009] Optionally, the acid includes at least one of hydrochloric acid, sulfuric acid and phosphoric acid; the volume concentration of the acid is 5-10%; and the particle size of the activated carbon is 0.25-0.425 mm.

[0010] Optionally, the usage ratio of the activated carbon to the acid is 1 g:7-15 mL.

[0011] Optionally, the activation reaction is carried out at a temperature of 25 to 35° C. and for a time of 16 to 24 hours.

[0012] Optionally, the copper salt solution comprises a copper sulfate solution or a copper nitrate solution, the concentration of the copper salt solution is 0.2-0.5 g / L, and the dosage ratio of the pretreated activated carbon to the copper salt solution is 1 g:80-120 mL.

[0013] Optionally, the immersion temperature is 24-26° C. and the immersion time is 5-7 hours.

[0014] Optionally, the dosage ratio of the copper ion-loaded activated carbon to water is 1 g: 3 to 6 mL.

[0015] Optionally, the microwave treatment has a power of 500 to 1000 W and a time of 2 to 4 min.

[0016] The present invention also provides modified activated carbon prepared by the above preparation method.

[0017] The present invention also provides application of the modified activated carbon in removing sulfadimethoxine from water.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The present invention provides a method for preparing modified activated carbon, wherein the pretreated activated carbon is immersed in a copper salt solution, and then the thermoelectric effect and heating effect of microwaves are used to change the pore structure of the activated carbon and form copper oxide on the surface, and activated carbon modified with copper ions is obtained after washing. The method does not require calcination at high temperature, and the microwave treatment time is short, which reduces energy consumption and avoids waste of resources.

[0020] The present invention modifies the pretreated activated carbon by microwave loading, so that the low-quality activated carbon with poor adsorption performance can be transformed into a stable activated carbon with a surface loaded with trace copper oxide (denoted as MCu). x O@AC), which has the characteristics of high specific surface area and high adsorption performance. The copper metal doping content in the activated carbon is only about 0.7%, but it can effectively adsorb sulfadimethoxine in water, and there is no heavy metal ion residue in the treated water, avoiding the problem of secondary pollution to the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 AC and MCu in the embodiment of the present invention x O@AC and Cu in the comparative example x XRD pattern of O@AC;

[0022] Figure 2 PAC, MCu in the embodiment of the present invention x O@AC and Cu in the comparative example x XPS survey spectrum of O@AC;

[0023] Figure 3 PAC, MCu in the embodiment of the present invention x O@AC and Cu in the comparative example x Carbon element spectrum peak diagram of O@AC, where (a) is the carbon element spectrum peak diagram of PAC, and (b) is the carbon element spectrum peak diagram of Cu x Carbon element spectrum of O@AC, (c) MCu x Carbon element spectrum of O@AC;

[0024] Figure 4 PAC, MCu in the embodiment of the present invention x O@AC and Cu in the comparative example x Oxygen element spectrum of O@AC, where (a) is the oxygen element spectrum of PAC, and (b) is the oxygen element spectrum of Cu x Oxygen element spectrum of O@AC, (c) MCu x Oxygen element spectrum peak diagram of O@AC;

[0025] Figure 5 PAC, MCu in the embodiment of the present invention x O@AC and Cu in the comparative example x Copper element spectrum peak diagram of O@AC, where (a) is the copper element spectrum peak diagram of PAC, and (b) is the copper element spectrum peak diagram of Cu x Copper element spectrum of O@AC, (c) MCu x Copper element spectrum peak diagram of O@AC;

[0026] Figure 6 AC, PAC, MCu in the embodiment of the present invention x O@AC and Cu in the comparative example x Fourier transform infrared spectra of O@AC, where (a) is the Fourier transform infrared spectra of AC, (b) is the Fourier transform infrared spectra of PAC, and (c) is the Fourier transform infrared spectra of Cu x Fourier transform infrared spectrum of O@AC, (d); MCu x Fourier transform infrared spectrum of O@AC;

[0027] Figure 7 AC, PAC, MCu in the embodiment of the present invention x O@AC and Cu in the comparative example x SEM images of O@AC, where (a) is the SEM image of AC, (b) is the SEM image of PAC, and (c) is the SEM image of Cu x SEM image of O@AC, (d); MCu x SEM image of O@AC;

[0028] Figure 8: The EDS graph of PAC in the embodiment of the present invention, wherein (a) is the distribution graph of copper and oxygen in PAC, (b) is the distribution graph of carbon, (c) is the distribution graph of oxygen, (d) is the distribution graph of copper, (e) is the total number spectrum of the distribution graph, and (f) is the graph of carbon, oxygen, and copper content;

[0029] Fig. 9 Cu in the comparative example of the present invention x EDS image of O@AC, where (a) copper and oxygen elements are in Cu x Distribution diagram of O@AC, (b) is the distribution diagram of carbon element, (c) is the distribution diagram of oxygen element, (d) is the distribution diagram of copper element, (e) is the total number spectrum of distribution diagram, and (f) is the carbon, oxygen and copper content diagram;

[0030] Fig.10 MCu in the embodiment of the present invention x EDS image of O@AC, where (a) copper and oxygen elements are in MCu x The mapping diagram in O@AC, (b) is the distribution diagram of carbon element, (c) is the distribution diagram of oxygen element, (d) is the distribution diagram of copper element, (e) is the total number spectrum of distribution diagram, and (f) is the carbon, oxygen and copper content diagram;

[0031] Fig.11 PAC, MCu in the embodiment of the present invention x O@AC and Cu in the comparative example x Adsorption-desorption isotherms of O@AC;

[0032] Fig.12 PAC, MCu in the embodiment of the present invention x O@AC and Cu in the comparative example x Pore ​​size distribution diagram of O@AC;

[0033] Fig.13 This is a process flow chart of the microwave loading method in an embodiment of the present invention;

[0034] Fig.14 PAC, MCu in the embodiment of the present invention x O@AC and Cu in the comparative example x Adsorption diagram of O@AC on SMZ. DETAILED DESCRIPTION

[0035] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0036] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0037] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0038] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0039] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0040] The raw materials used in the present invention can be obtained from the market or prepared by the existing technology.

[0041] The present invention provides a method for preparing modified activated carbon, comprising the following steps:

[0042] 1) Mixing activated carbon with acid to perform activation reaction to obtain pretreated activated carbon;

[0043] 2) impregnating the pretreated activated carbon in a copper salt solution to obtain activated carbon loaded with copper ions;

[0044] 3) Mixing the copper ion-loaded activated carbon with water and subjecting it to microwave treatment to obtain modified activated carbon.

[0045] The present invention firstly mixes activated carbon with acid to perform activation reaction to obtain pretreated activated carbon;

[0046] In some embodiments of the present invention, the activated carbon is cleaned before use; there is no particular limitation on the cleaning method, as long as the attached matter on the surface of the activated carbon can be removed. In an embodiment of the present invention, the activated carbon is cleaned with distilled water.

[0047] In the present invention, there is no particular limitation on the method of mixing the activated carbon and the acid, as long as the raw materials can be mixed uniformly. In an embodiment of the present invention, the mixing is oscillating mixing, the rotation speed of the oscillating mixing is 120 r / min, and the time is 16 h.

[0048] In some embodiments of the present invention, after the activation reaction is completed, the reaction liquid obtained by the activation reaction is subjected to solid-liquid separation, and the solid obtained by the solid-liquid separation is washed and dried in sequence to obtain pretreated activated carbon. The present invention does not specifically limit the methods of solid-liquid separation, washing and drying, and conventional solid-liquid separation methods, washing and drying methods can be used. In an embodiment of the present invention, the solid-liquid separation method is filtration, the washing is washing with distilled water until neutral, and the drying temperature is 100°C and the time is 24h.

[0049] In some embodiments of the present invention, the acid includes at least one of hydrochloric acid, sulfuric acid and phosphoric acid, preferably hydrochloric acid; the hydrochloric acid is preferably purchased from Tianjin Damao Chemical Reagent Factory; the volume concentration of the acid is 5-10%, for example, it can be 5%, 6%, 7%, 8%, 9%, 10%, etc.; the activated carbon particle size is 0.25-0.425mm. In an embodiment of the present invention, the activated carbon particle size is obtained by passing the activated carbon particles through a 40-mesh sieve, selecting the undersize, then passing the undersize through a 60-mesh sieve, and selecting the oversize.

[0050] In the present invention, the activation treatment can effectively remove some impurities and pollutants adsorbed by the activated carbon during production, transportation and storage, open the pores of the activated carbon, and improve the performance of the activated carbon.

[0051] In the embodiments of the present invention, hydrochloric acid is preferably used because: hydrochloric acid can effectively dissolve and remove inorganic impurities (such as metal oxides and carbonates) in activated carbon, thereby improving its purity; and hydrochloric acid is a widely used and relatively low-cost chemical reagent, which is suitable for large-scale production.

[0052] In the present invention, there is no particular limitation on the type of activated carbon, but coal-based activated carbon produced by Shanxi Xinhua Chemical Plant is preferred.

[0053] In some embodiments of the present invention, the dosage ratio of the activated carbon and the acid is 1g:7-15mL, specifically 1g:7mL, 1g:9mL, 1g:10mL, 1g:12mL, 1g:13mL and 1g:15mL.

[0054] In some embodiments of the present invention, the activation reaction temperature is 25-35°C, preferably 26-32°C, more preferably 28-30°C, and the time is 16-24h, preferably 20-22h.

[0055] After obtaining the pretreated activated carbon, the present invention immerses the pretreated activated carbon in a copper salt solution to obtain activated carbon loaded with copper ions.

[0056] In some embodiments of the present invention, after the pretreated activated carbon is impregnated in a copper salt solution, the impregnated activated carbon is washed and dried in sequence before being used in the next step. The present invention does not specifically limit the method of removing the impregnated activated carbon from the impregnation solution, and a conventional solid-liquid separation method, such as filtration, can be used. The present invention does not limit the washing method, and the impregnated activated carbon can be washed to neutrality. In an embodiment of the present invention, the impregnated activated carbon is washed with distilled water to neutrality. The present invention does not specifically limit the drying method, and dry pretreated activated carbon can be obtained. In an embodiment of the present invention, the drying temperature is 100°C and the time is 24 hours.

[0057] In some embodiments of the present invention, the copper salt solution includes a copper sulfate solution or a copper nitrate solution, preferably a copper sulfate solution. The copper sulfate solution is purchased from Tianjin Damao Chemical Reagent Factory, and the concentration of the copper salt solution is 0.2-0.5 g / L, preferably 0.3 g / L. The dosage ratio of the pretreated activated carbon and the copper salt solution is 1 g: 80-120 mL, specifically 1 g: 80 mL, 1 g: 90 mL, 1 g: 100 mL, 1 g: 110 mL and 1 g: 120 mL.

[0058] In some embodiments of the present invention, the immersion temperature is 24-26° C., specifically 24° C., 25° C. and 26° C., and the immersion time is 5-7 h, specifically 5 h, 6 h and 7 h.

[0059] In the present invention, the pretreated activated carbon is impregnated in a copper salt solution, and copper ions are introduced into the pretreated activated carbon.

[0060] After obtaining the copper ion-loaded activated carbon, the present invention mixes the copper ion-loaded activated carbon with water and performs microwave treatment to obtain modified activated carbon.

[0061] In some embodiments of the present invention, the microwave treatment is performed under condensation reflux conditions.

[0062] In the present invention, there is no special limitation on the equipment for microwave treatment, as long as it can generate microwaves. In the embodiment of the present invention, it is carried out in a microwave oven of model Midea M1-L213B.

[0063] In some embodiments of the present invention, the dosage ratio of the copper ion-loaded activated carbon to water is 1 g:3-6 mL, preferably 1 g:4 mL.

[0064] In some embodiments of the present invention, the power of the microwave treatment is 500-1000 W, preferably 600-900 W, more preferably 700-800 W, and the time is 2-4 min, preferably 2 min.

[0065] In the present invention, the activated carbon loaded with copper ions is subjected to microwave modification. During the microwave process, the divalent copper on the activated carbon uses carbon as a reducing agent and is reduced to monovalent copper under the action of microwaves. However, due to the presence of oxygen in the process, part of the monovalent copper is oxidized to divalent copper, which are finally combined with O2 in the air, and copper oxide and cuprous oxide are successfully loaded on the surface of the activated carbon.

[0066] In some embodiments of the present invention, after the microwave treatment is completed, the microwave-treated reaction liquid is naturally cooled to room temperature, solid-liquid separation is performed, and then the obtained solid is washed and dried in sequence to obtain modified activated carbon. The present invention does not specifically limit the method of solid-liquid separation, as long as the solid can be separated. In the embodiment of the present invention, the method of solid-liquid separation is filtration. The present invention does not limit the washing method, as long as the impregnated activated carbon can be washed to neutrality. In the embodiment of the present invention, the microwave-treated product is washed with distilled water to neutrality. The present invention does not specifically limit the drying method, as long as a dried washed product can be obtained. In the embodiment of the present invention, the drying temperature is 100°C and the time is 24h.

[0067] The present invention also provides modified activated carbon prepared by the above preparation method.

[0068] The present invention also provides application of the modified activated carbon in removing sulfadimethoxine (SMZ) from water.

[0069] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0070] Example 1

[0071] 1) 10 g of coal-based activated carbon (AC) with a particle size of 0.25 to 0.425 mm was washed with distilled water and placed in a 250 mL conical flask, 100 mL of a 5% HCl solution was added, and the mixture was shaken for 960 min at 25° C. and a rotation speed of 120 r / min for activation reaction. After the activation reaction was completed, the activated activated carbon was taken out by filtration, washed with distilled water until neutral, and dried at 100° C. for 24 h to obtain pretreated activated carbon (PAC);

[0072] 2) 1 g of pretreated activated carbon was placed in a conical flask beaker containing 100 mL of 0.5 g / L Cu2SO4 aqueous solution, immersed in a constant temperature water bath at 25°C for 6 h, the immersed activated carbon was taken out by filtration, the immersed activated carbon was washed with distilled water until neutral, and dried at 100°C for 24 h to obtain activated carbon loaded with copper ions;

[0073] 3) The copper ion-loaded activated carbon and 4 mL of water were added to a round-bottom flask, and the flask was placed in a microwave oven (Midea M1-L213B). The microwave power was set to 700 W. The activated carbon was microwaved for 2 min under condensation reflux conditions, then cooled to room temperature and filtered to obtain microwave-treated activated carbon. The microwave-treated activated carbon was washed with distilled water until neutral and then dried at 100 ° C for 24 h to obtain modified activated carbon (denoted as MCu x O@AC).

[0074] Comparative Example 1

[0075] Pretreated activated carbon was prepared according to the method of step (1) of Example 1. 1 g of pretreated activated carbon was weighed and placed in 100 mL of 1 g / L CuSO4 solution. Ultrasonication was performed at 140 W for 15 min. The pH was adjusted to 7 with NaOH solution and the mixture was allowed to stand for 15 min. The metal-loaded activated carbon (denoted as Cu) was obtained. x O@AC).

[0076] AC and MCu of Example 1 of the present invention x O@AC and Cu prepared in Comparative Example 1 x The XRD spectrum of O@AC was tested, and the test results are as follows Figure 1 As shown by Figure 1 It can be seen that the diffraction peak of carbon 2θ=26.5° appears in the XRD patterns of different activated carbons (such as Mark), indicating that the original support structure of activated carbon has not changed significantly. x O@AC and Cu x The diffraction peaks of O@AC at 2θ=35.6° and 42.3° are attributed to CuO (PDF 80-1916) and Cu2O (PDF 78-2076), respectively, indicating that the microwave loading method and the calcination loading method can also load copper on the activated carbon surface in the form of cupric oxide and cuprous oxide.

[0077] AC, PAC, MCu of Example 1 of the present invention x O@AC and Cu prepared in Comparative Example 1 x O@AC was tested by XPS. The results are as follows Figure 2-5 As shown by Figure 2 It can be seen that compared with PAC, MCu xO@AC and Cu x O@AC showed a Cu2p photoelectron peak 22 at a binding energy of 934.2 eV, proving the presence of Cu elements on the surfaces of MCuxO@AC and CuxO@AC.

[0078] Depend on Figure 3 From (a), (b), and (c) in Figure 1, it can be seen that the C1s peak results of the activated carbon before and after modification are almost unchanged. Figure 4 The O element peak fitting diagram O1s in (a), (b), and (c) shows that there are three fitting peaks on the PAC surface, such as H2O and O2 loosely bound oxygen species (531.6eV), 2627, CO (532.4eV), and C=O (533.08eV). The peak at 531.6eV is reduced after modification, indicating that the high temperature heating during the modification process reduces the loosely bound oxygen species of H2O and O2 on the surface of activated carbon, and Cu x O@AC at 530.85 eV (7.41%) and MCu x O@AC shows a peak of lattice oxygen of copper oxide at around 530.82 eV (4.17%), which indicates that copper oxide exists on the surface of the modified activated carbon and is closely related to Cu x O@AC vs MCu x O@AC loaded less copper oxide.

[0079] Depend on Figure 5 The Cu2P spectra in (a), (b), and (c) show that the presence of Cu in PAC is basically undetectable before loading, while MCu x O@AC and Cu x The Cu2p high binding energy end of O@AC has an obvious shock peak, indicating that there is Cu 2+ It exists, but its peak shape is wide and has obvious asymmetry, indicating that the existence form of Cu species on the surface of activated carbon is relatively complex. The results of Cu2p peak decomposition show that the copper in the sample exists in two forms, with a binding energy of 934.2eV corresponding to Cu 2+ , it can be attributed to CuO; and the low binding energy of 932.7eV corresponds to low-valent Cu2O, indicating that a part of Cu 2+ Reacts with the acidic oxygen-containing functional groups on the surface of activated carbon and is reduced to Cu + .

[0080] The contents of various elements in different activated carbons were calculated based on the XPS test results, as shown in Table 1.

[0081] Table 1 Contents of elements in PAC, MCuxO@AC and CuxO@AC

[0082]

[0083] AC, PAC, MCu of Example 1 of the present invention x O@AC and Cu prepared in Comparative Example 1 x O@AC was tested by FT-IR, and the test results are as follows Figure 6 As shown by Figure 6 It can be seen that the surface functional groups affect the adsorption performance of activated carbon. The FT-IR spectra of all samples have similar adsorption peaks, indicating that the chemical properties of modified activated carbon and original activated carbon should be similar in chemical composition. x O@AC and MCu x O@AC at 3442cm -1 The corresponding OH stretching vibration peak intensity of the hydroxyl functional group gradually weakens, which may be due to the strong acid or high temperature causing the OH to break. In addition, compared with PAC, Cu x O@AC and MCu x O@AC in the spectrum at 530 cm -1 Peaks appear on both sides, corresponding to the typical peaks of metal-O, indicating that copper may be loaded on the surface of activated carbon in the form of copper oxide to obtain MCu x O@AC. This is consistent with the XPS analysis.

[0084] The AC, PAC, and MCu of Example 1 of the present invention were tested. x O@AC and Cu prepared in Comparative Example 1 x The SEM results of O@AC are as follows Figure 7 As shown by Figure 7 As shown in (a), there are a small amount of pores and a large amount of impurities on the surface of AC. After hydrochloric acid pretreatment, as shown in (b) in 7, the impurities on the surface of PAC are almost removed, and a pore structure appears, but the surface is relatively rough and the pores are uneven in size. Figure 7 (c) in the figure shows that Cu x The surface pores of O@AC become larger and non-uniform. Figure 7 (d) in the figure shows that MCu x The surface of O@AC is relatively clean and smooth compared to Cu x O@AC has more pores and a relatively uniform pore structure. After the activated carbon is modified by the two methods, many micropores are sintered at high temperature during the modification process, causing the micropores to merge into mesopores and macropores with smooth inner walls, resulting in a corresponding decrease in the total pore volume and micropore volume.

[0085] The PAC and MCu of Example 1 of the present invention were tested. x O@AC and Cu prepared in Comparative Example 1 x EDS of O@AC. The content and morphology of copper loaded on the surface of activated carbon were determined by EDS. The test results are shown in Figure 8-10 As shown in Table 2, Figure 8 From (e), (f) and Table 2, we can see that PAC contains only carbon (92.5%) and oxygen (7.5%), but no copper. Fig. 9 From (e) and (f), we can see that Cu x The mass fraction of Cu in O@AC is 3.7%, Fig.10 From (e) and (f), we can see that the mass fraction of Cu in MCuxO@AC is 0.7%, indicating that MCu x O@AC was successfully prepared, which is consistent with the XPS analysis.

[0086] As shown in Table 2, compared with PAC, the surface C content of CuxO@AC and MCuxO@AC is reduced, which is due to the clogging of copper oxides or the filling of activated carbon pores, while the O content is increased, which is due to the combination of oxygen in the air and C and Cu on the surface of activated carbon during the loading process. Fig. 9 (c)Cu x Distribution diagram of oxygen element in O@AC. Fig. 9 Medium (d)Cu x The distribution of copper in O@AC is shown in Figure 2. Fig.10 (c) MCu x Distribution diagram of oxygen element in O@AC. Fig.10 Middle (d) MCu x The distribution diagram of copper element in O@AC shows that the positions of copper element and oxygen element coincide with each other, and the distribution of copper element matches the distribution of oxygen element, which indicates that copper exists as copper oxide on activated carbon. Moreover, the green fluorescent points representing copper are distributed evenly, indicating that the copper oxide loaded on the surface of activated carbon is well distributed evenly. This is consistent with the above analysis.

[0087] Table 2PAC, MCu x O@AC and Cu x Content of each element in O@AC

[0088]

[0089] AC, PAC, MCu of Example 1 of the present invention were analyzed by BET. x O@AC and Cu prepared in Comparative Example 1 x The pore structure of O@AC was analyzed, among which the N2 adsorption-desorption isotherms of activated carbon before and after modification were as follows: Fig.11 The pore size distribution diagram is shown in Fig.12 As shown in Table 3, the pore structure parameters are shown.

[0090] The structure of activated carbon determines its adsorption capacity. According to IUPAC classification, Fig.11The adsorption-desorption curves of the three activated carbons combine type I and type II, p / p0<0.02, and the N2 adsorption of all samples increases sharply with the increase of P / P0 and tends to saturation, indicating that there are a large number of micropores (diameter <2nm) in the material; the hysteresis loop at a relative pressure of 0.5-1 indicates that the activated carbon has an obvious slit-like mesopore structure. Fig.12 The pore size distribution curve also shows that all samples are mainly micropores with some mesopores, which is consistent with the SEM characterization results.

[0091] from Fig.11 As can be seen from Table 3, compared with PAC, Cu x O@AC and MCu x The N2 saturation adsorption capacity of O@AC decreased, and the modified activated carbon Cu x O@AC and MCu x The specific surface area and total pore volume of O@AC decreased, with the specific surface area decreasing by 4.51% and 1.01%, the total pore volume decreasing by 3.84% and 3.31%, and the porosity decreasing by 2.59% and 1.38%. This is due to the collapse of some pores of activated carbon during high-temperature calcination and microwave heating, and the Cu-containing oxides loaded in the pores and on the surface of the modified activated carbon blocking part of the pore structure of the activated carbon, which is consistent with the SEM characterization results.

[0092] Table 3AC, PAC, Cu x O@AC、MCu x Pore ​​structure parameters of O@AC

[0093]

[0094] The present invention has a great influence on PAC and MCu x O@AC and Cu x The adsorption capacity of sulfadimethoxine by O@AC was tested. 100 mg PAC, 100 mg MCu x O@AC and 100 mg Cu x O@AC was placed in 100 mL of 20 mg / L SMZ aqueous solution and adsorbed at 30 °C. Fig.14 shown.

[0095] Fig.14 Figure 2 is the adsorption diagram of SMZ by different activated carbons. x O@AC、MCu xThe adsorption capacity of SMZ on O@AC was 18.06 mg / g and 17.64 mg / g, respectively, which was 24.07% and 21.16% higher than that on PAC (14.56 mg / g). BET analysis showed that the specific surface area and total pore volume before and after loading were similar, but the adsorption capacity of SMZ was enhanced because SMZ contained groups with lone pair electrons such as -NH2, -NH and -N, which combined with the empty orbitals of copper atoms in copper oxide and cuprous oxide through coordination to enhance the adsorption performance. That is, the Cu loaded on the surface of activated carbon x O forms new active sites and specifically adsorbs SMZ.

[0096] Weigh 100 mg Cu x O@AC and MCu x O@AC was placed in 100 mL of 20 mg / L SMZ solution and shaken in a constant temperature water bath oscillator at pH = 6 and 30 °C for 240 min. The supernatant was then filtered with a 0.22 μm filter membrane and the copper ion content in the solution was measured using an ICP-OES: Agilent 5110 instrument. The results showed that MCu x Cu in the solution after O@AC adsorbed SMZ 2 + The content is 0.846 mg / L, much lower than Cu x After O@AC adsorbed SMZ, Cu 2+ content (2.046mg / L), and meets the Class II discharge standard for copper (<1.0mg / L) in the National Surface Water Environmental Quality Standard (CB 3838-2002) and the secondary discharge requirement for total copper in wastewater discharged by all pollutant discharge units in the National Integrated Sewage Discharge Standard (CB 89781996) (<1.0mg / L).

[0097] From the above content, we can see that Cu x The copper content in O@AC is 3.7%, MCu x The copper ion content in O@AC is only 0.7%, but Cu x O@AC and MCu x The adsorption amount of O@AC on SMZ is not much different, indicating that the impregnation microwave method can effectively improve the adsorption performance of activated carbon on SMZ, and the preparation method is simple and has lower energy consumption than the impregnation calcination method. x O@AC has a lower copper ion load and less heavy metal ion residue in the wastewater, thus avoiding the problem of secondary pollution.

[0098] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing modified activated carbon, characterized in that: The following steps are involved: 1) Mixing activated carbon with acid to perform activation reaction to obtain pretreated activated carbon; 2) impregnating the pretreated activated carbon in a copper salt solution to obtain activated carbon loaded with copper ions; 3) Mixing the copper ion-loaded activated carbon with water and subjecting it to microwave treatment to obtain modified activated carbon.

2. The preparation method according to claim 1, characterized in that: The acid comprises at least one of hydrochloric acid, sulfuric acid and phosphoric acid; the volume concentration of the acid is 5-10%; and the particle size of the activated carbon is 0.25-0.425 mm.

3. The preparation method according to claim 1 or 2, characterized in that: The usage ratio of the activated carbon to the acid is 1g:7-15mL.

4. The preparation method according to claim 3, characterized in that: The activation reaction is carried out at a temperature of 25 to 35° C. and for a time of 16 to 24 hours.

5. The preparation method according to claim 1, characterized in that: The copper salt solution includes a copper sulfate solution or a copper nitrate solution; the concentration of the copper salt solution is 0.2-0.5 g / L, and the dosage ratio of the pretreated activated carbon to the copper salt solution is 1 g:80-120 mL.

6. The preparation method according to claim 1 or 5, characterized in that: The immersion temperature is 24-26° C. and the immersion time is 5-7 hours.

7. The preparation method according to claim 6, characterized in that: The usage ratio of the copper ion-loaded activated carbon to water is 1 g:3-6 mL.

8. The preparation method according to claim 7, characterized in that: The power of the microwave treatment is 500-1000W, and the time is 2-4 minutes.

9. A modified activated carbon prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the modified activated carbon according to claim 9 in removing sulfadimethoxine from water.